Demographic and psychosocial factors associated with the decision to learn mutation status in familial frontotemporal dementia and the impact of disclosure on mood. (1st February 2022) - Bajorek, Lynn P.; Kiekhofer, Rachel; Hall, Matthew; Taylor, Joanne; Lucente, Diane E; Brushaber, Danielle; Appleby, Brian; Coppolla, Giovanni; Bordelon, Yvette M; Botha, Hugo; Dickerson, Brad C; Dickson, Dennis W; et al.
Abstract: Background: Up to 30% of frontotemporal dementia (FTD) cases are due to known pathogenic mutations (f‐FTD). Little is known about the factors that predict who will choose to learn their results. Upcoming clinical trials in f‐FTD may require disclosure prior to enrollment, even before symptom onset, and thus characterizing this sample is important. Furthermore, understanding the mood impacts of genetic disclosure may guide genetic counseling practice. Method: F‐FTD participants (n=568) from families with a known pathogenic mutation ( MAPT, C9orf72, GRN ) were enrolled through the ARTFL/LEFFTDS Longitudinal FTD Study (ALLFTD) and provided the opportunity for disclosure. Independent‐sample t‐tests compared demographic and psychosocial factors between participants who did and did not receive their results. In participants who were asymptomatic at baseline and follow up (n=199, 177 with follow‐up), linear mixed effects modeling was used to investigate pre‐ to post‐disclosure changes in the 15‐item Geriatric Depression Scale (GDS). Result: Of participants from families with a known pathogenic genetic mutation, 47% received genetic disclosure. Of the asymptomatic subset (n=386), 36% know their mutation status. Of these asymptomatic learners, 46% received disclosure through the study, and the remainder learned their genetic status prior to study enrollment. None of the analyzed demographic or psychosocial factors (i.e., sex, age, education, having children) differed between learners and non‐learners (p's > 0.05). In the longitudinal analysis of asymptomatic participants, learners showed a pre‐ to post‐increase of 0.31 GDS points/year (95%CI: ‐0.08, 0.69, p = 0.12), whereas non‐learners showed a slight decline (‐0.15 points/year, 95%CI: ‐0.36, 0.06, p = 0.16). This difference between slopes was statistically significant (0.46, 95%CI: 0.02, 0.89, p=0.04) but represents a small clinical effect. In asymptomatic learners, slopes did not differ based on mutation status (0.28, 95%CI: ‐0.66, 1.20, p=0.55). Conclusions were based on the estimates and full range of confidence intervals. Conclusion: The majority of asymptomatic research participants do not know their genetic status, which will be a consideration for clinical trials that require disclosure. No considered demographic factors were strongly associated with the decision to receive disclosure. The findings suggest that disclosure in asymptomatic participants has minimal impact on depressive symptoms regardless of genetic results.